Let's solve the equation \(2x - 5 = 3(4x + 5)\) step by step according to your instructions.
Step 1: Distributing Property
We'll start by distributing \(3\) on the right side of the equation:
\[ 2x - 5 = 3(4x) + 3(5) \] \[ 2x - 5 = 12x + 15 \]
Step 2: Move Variables to One Side of the Equation
Next, we want to move all the \(x\) terms to one side. We'll choose to subtract \(12x\) from both sides:
\[ 2x - 5 - 12x = 12x + 15 - 12x \] \[ 2x - 12x - 5 = 15 \] \[ -10x - 5 = 15 \]
Step 3: Move Constants to the Other Side of the Equation
Now, we will add \(5\) to both sides to isolate the term with \(x\):
\[ -10x - 5 + 5 = 15 + 5 \] \[ -10x = 20 \]
Step 4: Isolate Your Variable (Creation/Division of Properties)
Finally, we will divide both sides by \(-10\) to solve for \(x\):
\[ x = \frac{20}{-10} \] \[ x = -2 \]
Conclusion
The solution to the equation \(2x - 5 = 3(4x + 5)\) is:
\[ \boxed{-2} \]
If you have any further questions or need additional explanations, feel free to ask!